Typification of three names in Justicia L. (Acanthaceae) - Soumya, Puliyakode; Sunojkumar, Purayidathkandy (Phytotaxa, 2019)
Three names in Justicia (Acanthaceae), J. glabra, J. bojeri, and J. rusbyi are lectotypified.